An unusual case of necrotizing pneumonia in a healthy apnea diver - Beyer, Christian; Alsalameh, Rayya; Bogdan, Christian; Ganslmayer, Marion; Neurath, Markus; Strauss, Richard; Fürst, Julia (Infection, 2025)
We report a case of necrotizing pneumonia caused by hypervirulent Klebsiella pneumoniae in an athletic, 54-year-old apnea diver. Since hypervirulent Klebsiella pneumoniae strains prevail in Southeast Asia and are mainly associated with “invasive liver abscess syndrome”, we considered and tested for hypervirulence only when the necrotizing pneumonia turned out to be refractory to initial antibiotic treatment. Although the hypervirulent Klebsiella pneumoniae strain in our patient did not show multi-drug resistance, a total of 6 months of high-dose antibiotic therapy was necessary to cure the infection.
CRIS-Team Scopus Importer:2025-08-15
Keywords: Difficult-to-treat; Hypervirulent Klebsiella pneumoniae; Pneumonia; Virulence factors